"Letters to the twenty-first century botanist. Second series: "What is a seed? – 2. Regulation of desiccation tolerance and longevity in developing seeds: two faces of the same coin". Issue 2 (3rd April 2018) - Buitink, Julia; Leprince, Olivier
ABSTRACT: Desiccation tolerance and longevity are two essential properties that enable seeds to ensure the plant life cycle. Desiccation tolerance is defined as the ability to tolerate a rapid drying that brings the seed moisture content in equilibrium with ambient air, whereas longevity is the capacity to remain alive in the dry state over long periods. Both properties are progressively acquired during seed development and are of considerable agronomic and ecological relevance. Here, we argue that desiccation tolerance and longevity should be considered and studied separately. Recent progress in elucidating the protective and regulatory mechanisms contributing to these two aspects of seed survival in the dry state is presented.